Survival in homozygous familial hypercholesterolaemia is determined by the on-treatment level of serum cholesterol. (1st July 2017) - Thompson, Gilbert R; Blom, Dirk J; Marais, A David; Seed, Mary; Pilcher, Gillian J; Raal, Frederick J
Abstract: Aims: Homozygous familial hypercholesterolaemia (FH) is a rare inherited disorder characterized by extreme hypercholesterolaemia from birth, accelerated atherosclerosis, and premature death. Many forms of lipid-lowering therapies have been used in the past, but definitive evidence of benefit has been lacking. We therefore undertook a retrospective survey of lipid levels and clinical outcomes of FH homozygotes treated with a combination of lipid-lowering measures between 1990 and 2014 in South Africa and the UK. Methods and results: We divided 133 previously statin-naive homozygotes into quartiles according to their on-treatment levels of serum cholesterol and compared the occurrence of any death, cardiovascular death, and major adverse cardiovascular events (MACE) between the quartiles during 25 years of follow-up, using Cox and competing risks regression analysis. Patients in Quartile 4, with an on-treatment serum cholesterol >15.1 mmol/L, had a hazard ratio of 11.5 for any death compared with those in Quartile 1, with an on-treatment cholesterol of < 8.1 mmol/L. Those in Quartiles 2 and 3 combined, with on-treatment cholesterol of 8.1–15.1 mmol/L had a hazard ratio of 3.6 compared with Quartile 1. These differences were statistically significant ( P  < 0.001) and remained so after adjustments for confounding factors ( P  = 0.04). Significant differences between quartiles were also evident for cardiovascular deaths and MACE. Conclusion: These findings provide unequivocal evidence that the extent of reduction of serum cholesterol achieved by a combination of therapeutic measures, including statins, ezetimibe, lipoprotein apheresis, and evolocumab, is a major determinant of survival in homozygous FH.